PENGARUH KONSELING TEKNIK MENYUSUI YANG BENAR TERHADAP PENGETAHUAN DAN SIKAP MENYUSUI PADA IBU POST PARTUM DI WILAYAH KERJA PUSKESMAS RIJALI AMBON - Dewi Arwini Bugis; Saadia Matdoan; Dhamas Mega Amarlita (Pasapua Health Journal, 2020)
Introduction: Globally there are 40% of babies who are exclusively breastfed (WHO, 2017). The results of a survey by the Center for Disease Control and Prevention in the United States in 2014 showed that 40.7% of babies were exclusively breastfed until the age of three months and 18.8% of babies were exclusively breastfed until the age of six months. Meanwhile, the 2017 Indonesian Demographic and Health Survey was jointly carried out by the central agency and the ministry of health. Method: The research design used was a pre-experimental with a one group pretest – posttest design, namely a study in which there was no control group, but the first observation (pre-test) was carried out to find out the population in this study was the effect of correct breastfeeding technique counseling on knowledge and attitudes of breastfeeding in post partum mothers. In the working area of the Ambon Rijali Health Center with a total sample of 30 respondents.Results: the results of the analysis using the Wilcoxon Test on knowledge and attitudes, a value of p = 0.000 (p < 0.005) can be obtained, which means that there is an influence on knowledge and attitudes on breastfeeding mothers in the working area of the Rijali Ambon Health Center.